Defining Central American mini-cities with European covered passages’ fusion of spaces and times - Acosta Schnell, Sabrine (2021)
Central American mini-cities are described as new real-estate products in the beginning of the 21st century. “These are projects of private initiative that combine urban mixed uses, creating a multifunctional territory, materialized in a landscape and in a morphology determined by structuring elements that appeal to the principles of New Urbanism” (Acosta, 2020). Among their characteristics are their diversity of goods and services, functions and relationships. Their three basic uses are residential, commercial and entertainment. This letter suggests a novel proposal to characterize and define these recent urban forms, as part of the continuation of a broader and pioneering doctoral investigation (Acosta, 2020b) which had as a main goal dealing with “how mini-cities are participating in the process of urban restructuring by playing a compensatory role in the face of metropolitan challenges, introducing new socio-economic dynamics, modifying factual and symbolic centralities and changing commercial relationships between urbanites and other typologies” (p. 3). Its contribution is broad, tackling a wide variety of subjects within the urban geography local studies. This research suggests a deeper historical comparison between European covered passageways and mini-cities, in order to identify structural, behavioural, architectonic, economic, residential and social patterns, to contribute to a more solid definition of the real estate product. This is with the objective of avoiding a possible denial of their exceptionalism due to similarities with other broadly negatively criticized commercial and residential typologies inherited from the processes of globalization (malls and gated communities). The leisure and residential functional perspective will be proposed to be addressed later as part of this definition research